Volunteerism and Working with Volunteers - Senturk, Murat (Istanbul University Press, 2022)
The story of this book began at a meeting we held at the beginning of the summer (June 9) in 2014. At the meeting, we discussed how to popularize volunteerism at Istanbul University. We talked about the various practices we would be able to bring to life, but emphasized that, whatever we did, the practices needed to be research-based. Thus emerged the research on Istanbul University students' perceptions, tendencies, and experiences of volunteerism. During the process, we added various components to this research, which then turned into the book Üniversitede Gönüllü Olmak [Volunteering in Universities]. Based on this research, the Gönüllü Akademisi [Volunteer Academy] (a 10-week program consisting of activities such as seminars, workshops, film readings, and NGO visits) and the Gönüllü Ol İstanbul Platformu [Volunteer Istanbul Platform] (a platform aimed at established Istanbul University students for getting NGOs, projects, and campaigns seeking volunteers to meet and match up with those wanting to volunteer) were brought to life with the aim of increasing students' awareness on volunteerism. Of course, all the research and practices progressed through our student friends and all our volunteer work. From the very start, we endeavored to take care not to lose the nature of the studies done on volunteerism; we certainly don't know how well we succeeded. More than 1,000 students participated in both the Volunteer Academy and the volunteer activities we organized. In addition, the Civil Society and Volunteerism course became a new course within the Department of Sociology as well as an important elective course in which students showed interest. This was followed by the NGO and Social Responsibility Management non-thesis master's program that opened up within the Department of Sociology. This program is based on lectures given by experienced leading names in the NGO field. We are currently maintaining it as a program in which professionals who work in the sector, those who want to work in the NGO field, and volunteers participate. We've also organized panels and workshops on volunteering, NGOs, and relevant topics. We last conducted the Türkiye Gönüllük Araştırması [Research on Volunteerism in Turkiye] for the Ministry of Youth and Sports. In this context, we as Istanbul University continue to carry out studies in the field of volunteering and NGOs, popularize volunteering among students, and share knowledge and experience as well as develop relations and cooperation in the NGO field. One of the steps in preparing this book was the Volunteering in Universities Course Curriculum Workshop we organized at Istanbul University on April 18, 2018. People such as academicians, NGO professionals, volunteers, and student club representatives attended this workshop, in which we discussed the volunteerism curriculum in universities from a participatory perspective. The ideas the participants had at this workshop have played an important role in shaping the work at hand. The workshop report has been prepared, however, we are unable to publish it. We planned the next steps regarding the idea of elective courses in universities and the materials to be prepared for these courses. With the decision the Council of Higher Education made to establish the Volunteer Studies course as an elective in universities in April 2020, however, we returned to this work we had been unable to carry out at that time due to various agendas and accelerated our book studies. The process has taken a little longer due to the attention we gave to the inclusive and comprehensive nature of this work and our desire to address various topics, but it has finally been completed and here we are. Volunteerism and Working with Volunteers has the aim of presenting readers with many of the contexts and concepts related to volunteering by addressing volunteerism through its various dimensions in our day. Because each chapter is clear on its own, the book takes into account the dimensions that make volunteerism unique. This book claims that relating to the historical and social contexts of volunteerism is possible these days only if volunteerism is addressed in all its dimensions.